A STUDY ON BREW BASED MOBILE PSYCHOTEST IMPLEMENTATION - ANDRIYANTI (NIM 23206028), NOVITA
The use of mobile technology in performing psychotest has become a considerable feature nowadays. Some of the advantages are that the assessee would not have to directly interact with the assessors because the system has replace their position, and the test can be held at anytime, anywhere. This experimental research has developed and implemented the application of BREW based mobile psychotest. The system design was developed in BREW platform so it can be implemented to a BREW simulator, and in the end it is implemented to a cellular phone ZTE C330. Furthermore advanced research is conducted to solve a proposed hypothesis about the difference of given psychotest method to obtain various response which respect to feasibility aspect and groups of user satisfaction. The application trial was involving three groups of assessee which was also given a conventional psychotest as a comparation. Each groups consist of 30 person as samples from professional community, university students and civil servant candidates, and common peoples. After the trial, each person gave their comments and opinion about the application. The data is being statistically analyzed using t-Student Test to find out whether there are different responses towards the given psychotests methods. The experiment has proved that the mobile psychotest application (PsikoTest@Hand) can be implemented even to a simple using cellular phone like ZTE C330. The analysis result has shown a significant difference between the use of conventional psychotest and PsikoTest@Hand. We can see that from the average feasibility and user's satisfaction score for PsikoTest@Hand in each group. The professionals group has feasibility score 3,83 from ideal expectation scale in 5 or equals to 76,6% feasible, the students and civil servant candidates group has 4,03 from ideal expectation scale in 5, equals to 80,6% feasible, and the common peoples group has 4,07 from ideal expectation scale in 5, equals to 81,4% feasible. In the other hand, the average user’s satisfaction score for PsikoTest@Hand is a little bit higher. The professionals group satisfaction score is 4,17 from ideal expectation scale in 5 or equals to 83,4% satisfied, the students and civil servant candidates group has 4,20 from ideal expectation scale in 5, equals to 84,0% satisfied, and the common peoples group has 4,07 from ideal expectation scale in 5, which is mean 84,6% of the group satisfied with the product.